Local government capacities for the integration of migrants : good European experiences and practices - Đorđević, Snežana, politologinja (Array, 2018)
This paper explains the role of local governments (cities, regions) in the implementation of immigration policy in Europe. It covers the period since the 1960s and explains various waves and types of immigration, state policies, and the capacities of local government to help with immigrant integration. Several case studies are presented: Antwerp (Belgium), Malmö (Sweden), and Bologna and the Veneto region (Italy). The policy of migrant integration is exceedingly complex, requiring persistent dedication on part of all countries to mitigate the biggest problems of the contemporary globalised world (wealth distribution; poverty reduction; prevention of economic and political conflicts, especially wars; development of human rights; ecology), and to upgrade democratic capacities in each society. The contribution of this paper is to show that liberal policy in this field is the best option for the effective integration of migrants. Host state and local governments should be more sensitive to the nature and needs of the migrant population, and to foster a better understanding of the values, customs, and culture of both migrants and the domestic population. Useful measures which can help migrants in the process of integration are: tailored education, training for skills and jobs, participation in decision-making processes in the host country, and cooperation between the migrants’ home and host countries. It is important that political leaders continuously convey the message to the public that migrants represent great social capital and potential for the economic development of their society. The public should understand that in the contemporary globalised world society should be open to capital and labour migration, and that in this process our communities are given the chance to be multicultural, open, tolerant, and richer in every aspect.